Individualised pulse oximetry limits in neonatal intensive care. Issue 3 (1st November 1999) - Gupta, R; Yoxall, C W; Subhedar, N; Shaw, N J
Abstract : AIM: To determine whether individualised limits for arterial oxyhaemaglobin saturation by pulse oximetry (SpO2 ) are more effective for detecting hypoxia and hyperoxia in sick newborn infants than setting fixed limits. METHODS: Six hundred and ninety two simultaneous measurements of SpO2 and partial pressure of oxygen in arterial blood (PaO2 ) were made in 95 infants. The sensitivity and specificity for predicting hypoxia and hyperoxia using various fixed SpO2 limits and also individualised SpO2 limits, calculated using a standard equation, were determined and compared. RESULTS: None of the fixed limits for SpO2 was both sensitive and specific for predicting hypoxia and/or hyperoxia. There was no difference between these and individualised limits. CONCLUSION: Individualised SpO2 limits are no more effective than fixed SpO2 limits for predicting hypoxia and/or hyperoxia in sick newborn infants. SpO2 monitoring is not an ideal method for assessing PaO2 .